(untitled) (Research, Society and Development, 2021)
Objective: This study aims to report the experience of the development of the Health Caregivers Project in quilombola communities, in the training of lay caregivers in the Health Caregivers Project, in the state of Maranhão. Methodology: This is an experience report about the development and evaluation of the project for the formation of lay caregivers. Result: cases of hypertension and diabetes were detected and monitored in the community by caregivers, weekly, and referred to the Family Health Strategy for drug intervention. Conclusion: Through this experience, we found that it is possible to train lay caregivers with this workload and developed content, to keep quilombola communities in care and monitoring, regarding hypertension, diabetes mellitus and metabolic syndrome.